Bear ebook A novel. - Phillips, Julia (2024)
NATIONAL BESTSELLER • From the celebrated author of Disappearing Earth comes a tale of family, obsession, and a mysterious creature in the woods—“a mesmerizing story about hope, sisterhood, and survival with a truly shocking twist at the end” ( People, Book of the Week). NEW YORK TIMES BOOK REVIEW EDITORS’ CHOICE • A GOOD MORNING AMERICA BUZZ PICK! LONGLISTED FOR THE CAROL SHIELDS PRIZE FOR FICTION • A BEST BOOK OF THE YEAR: NPR, Vulture, Chicago Public Library “Thrilling and propulsive, glorious and terrifying. Julia Phillips is a brilliant writer.”—Ann Patchett “Beautiful and haunting . . . this is brilliant.”— Publishers Weekly (starred review) They were sisters and they would last past the end of time. Sam and Elena dream of another life. On the island off the coast of Washington where they were born and raised, they and their mother struggle to survive. Sam works on the ferry that delivers wealthy mainlanders to their vacation homes while Elena bartends at the local golf club, but even together they can’t earn enough to get by, stirring their frustration about the limits that shape their existence. Then one night on the boat, Sam spots a bear swimming the dark waters of the channel. Where is it going? What does it want? When the bear turns up by their home, Sam, terrified, is more convinced than ever that it’s time to leave the island. But Elena responds differently to the massive beast. Enchanted by its presence, she throws into doubt the desire to escape and puts their long-held dream in danger. A story about the bonds of sisterhood and the mysteries of the animals that live among us—and within us— Bear is a propulsive, mythical, richly imagined novel from one of the most acclaimed young writers in America.